ACCESSIBILITY STANDARD OF PRIMARY SCHOOL WITHIN KANKE LOCAL GOVERNMENT AREA OF PLATEAU STATE, NIGERIA - Bature, Y. A.; Barki, J. J. (FUDMA Journal of Sciences, 2023)
The relevance of site planning in journey to and from school revolves around accessibility. Rural residential location is a function of accessibility and distance. Town and school planners try to ensure pupils travel distance do not affect their academic performance, hence it’s stipulated <2km a walking distance. Accessibility affect planned structure of whether clustered or dispersed in the siting of social services. There are 4districts in Kanke LGA with public primary schools existing as Amper; 13, Ampang-east; 13, Garram; 12 and Kabwir 38 a total of 96 schools. There were no private schools during this research. A sample of 50% on each district were used for random school selection as Amper;7, Ampang-East;6, Garram;6 and Kabwir 19 to give a total of 48 sampled schools. A total of 2780 questionnaire were systematically randomly administered. Questionnaire had 2 subsections pupils travel: age, distance travel, effect of walking to and from school, travel hazard and transport modes and parents palliatives measures: reasons for low pupil assistance, etc. The 2 hypotheses used were Chi-square; school attendance is not a function of distance from home, had 26.68 using a double tailed test of df; 26.30 and 32.00 at 0.005 and 0.01 level of confident respectively. H1 is accepted; 69.68>32.00>26.30 as school attendance is a function of distance from pupil home. PCC test of distance reliability with 95% test of confidence; 0.05 revealed H2; School attendance is affected by distance. Commendation is school planners should comply with stipulated accessibility standard, the establishment of school clinic.